Effect of -ray irradiation on performance of LiNbO3-based piezoelectric vibration sensors. (1st December 2021) - Wei, Huifen; Geng, Wenping; Bi, Kaixi; Li, Tao; Li, Xiangmeng; Zhang, Huiyi; Li, Yudong; Xun, Mingzhu; Chou, Xiujian
Abstract: LiNbO3 (LN)-based micro-electro-mechanical systems (MEMS) vibration sensors exhibit giant perspectives in extreme environments, where a great amount of irradiation exists. However, to the best of our knowledge, it is still unknown whether the irradiation affects the performance of LN-based piezoelectric MEMS sensors. Based on this consideration, it is necessary to model the irradiation environment to investigate the effect of high-dosage irradiation on LN-based vibration sensors. Firstly, the theoretical work is done to study the Compton effect on the gamma-ray irradiation with a 60 Co source. After irradiation, X-ray diffraction (XRD) characterization is performed to verify the effect of irradiation on the crystalline of LN thin film. Meanwhile, the performances of output voltages on the five MEMS devices under various dosage of irradiation are compared. As a result, a neglected shift of 0.02 degrees is observed from the XRD image only under maximum irradiation dosage of 100 Mrad(Si). Moreover, the output voltages of cantilever beam vibration sensors decrease by 3.1%. Therefore, it is verified that the γ-ray irradiation has very little influence on the LN-based MEMS vibration sensors, which have great attraction on the materials and sensors under high-dose irradiation.